Pendampingan UMKM: Meningkatkan Daya Saing Dan Inovasi di Era Digital Pada UMKM Bintang Emas di Desa Kasengan, Kecamatan Manding, Kabupaten Sumenep - Moh. Kurdi; Dina Arifatun Nisa; Unsilatur Rahmah; Dewi Intan Andini; Riana Suci Ardianty; Muhammad Amir; Mohammad Ahsani Taqwim; Ary Wahyudi (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
The SME assistance program entitled "SME Assistance: Enhancing Competitiveness and Innovation in the Digital Era for Bintang Emas SMEs in Kasengan Village, Manding Subdistrict, Sumenep Regency" was implemented from March 1, 2024, to May 31, 2024. This program aims to enhance digital capacity, product innovation, and modern marketing strategies for Bintang Emas SMEs. Through digital marketing training, product innovation workshops, and technical assistance, participants learn to utilize digital technology and e-commerce platforms to enhance the visibility and sales of their products, including the flagship product of cassava chips. The results showed a 25% increase in sales in the first three months, an improvement in product variety and quality, as well as an enhancement in business and financial management skills. This program also successfully fostered a spirit of mutual cooperation and collaboration in the local community and strengthened the relationship between SMEs and the surrounding community. With these achievements, it is hoped that Bintang Emas SMEs will continue to innovate and adapt to market changes, providing sustainable benefits to the local economy and the welfare of the local community.